Integrated sample-to-detection chip for nucleic acid test assays. - Prakash, R.; Pabbaraju, K.; Wong, S.; Tellier, R.; Kaler, K. (Biomedical Microdevices, 2016)
Nucleic acid based diagnostic techniques are routinely used for the detection of infectious agents. Most of these assays rely on nucleic acid extraction platforms for the extraction and purification of nucleic acids and a separate real-time PCR platform for quantitative nucleic acid amplification tests (NATs). Several microfluidic lab on chip (LOC) technologies have been developed, where mechanical and chemical methods are used for the extraction and purification of nucleic acids. Microfluidic technologies have also been effectively utilized for chip based real-time PCR assays. However, there are few examples of microfluidic systems which have successfully integrated these two key processes. In this study, we have implemented an electro-actuation based LOC micro-device that leverages multi-frequency actuation of samples and reagents droplets for chip based nucleic acid extraction and real-time, reverse transcription (RT) PCR (qRT-PCR) amplification from clinical samples. Our prototype micro-device combines chemical lysis with electric field assisted isolation of nucleic acid in a four channel parallel processing scheme. Furthermore, a four channel parallel qRT-PCR amplification and detection assay is integrated to deliver the sample-to-detection NAT chip. The NAT chip combines dielectrophoresis and electrostatic/electrowetting actuation methods with resistive micro-heaters and temperature sensors to perform chip based integrated NATs. The two chip modules have been validated using different panels of clinical samples and their performance compared with standard platforms. This study has established that our integrated NAT chip system has a sensitivity and specificity comparable to that of the standard platforms while providing up to 10 fold reduction in sample/reagent volumes.